Measurement of Innovation: Where Do We Stand? (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2016)
Innovation is widely considered as the main determinant of long-term economic growth. Despite this consensus, it is arduous to measure its economic effect at the firm and aggregate level. The objective of the present paper is to propose a critical examination of innovation indicators and measures of the economic impact of innovation. All available innovation indicators fall short of measuring innovation and its economic effect. However, the future could be more promising as enterprises are moving to a more quantitative management. The ’datafication’ of their management could make available the information that innovation economists have long hoped for.This work is licensed under a Creative Commons Attribution-NonCommercial 4.0 International License.